JURNAL KESEHATAN GAMBARAN PENGGUNAAN OBAT ANALGESIK DI APOTEK XKOTA KEBUMEN PERIODE JANUARI-MARET 2021 - Rr. Erni Kusuma Putri (STIKES DUTAGAMA KLATEN, 2021)
Analgesic is a painkiller drugs for relieving and reducing pain sensation without provide anastetic effect. Among society analgesic drugs are the most used drugs because easy to get and become part of a lifestyle. The purpose of this study was to determine the percentage of analgesic NSAID drugs usage at pharmaciesX in Kebumen city at period January until March 2021. This study was a non-experimental descriptive study with a retrospective approach from January - March 2021. purposive sampling method was used, wich means to sampling with certain criteria. The data was taken from the recapitulation book of drug usage. The percentage of NSAID drugs usage from Diclofenac, Mefenamic Acid, Piroxicam and Meloxicam were, respectively 38% (7,920 pills), 31.14% (6,490 pills), 5,200 pills (24.95%) and (5.90%) 1,230 pills.